Modern Self- determination: The right to external autonomy after the Advisory Opinion on Kosovo - Indacochea Jauregui, Juan Manuel (Revista Tribuna Internacional, 2018)
In recent times, the international practice has provided new cases of mutually agreed secession, as well as violent ruptures. Although the unilateral secessions are not well received by the international community, they are possible and they have been favored by the Advisory Opinion on Kosovo.